Treatment of rare co‐occurrence of Epstein–Barr virus‐driven post‐transplant lymphoproliferative disorder and hemophagocytic lymphohistiocytosis after allogeneic stem cell transplantation. Issue 6 (1st September 2014) - Weber, T.; Wickenhauser, C.; Monecke, A.; Gläser, C.; Stadler, M.; Desole, M.; Ligeti, K.; Behrmann, C.; Müller‐Tidow, C.; Müller, L.P.
Abstract In both conditions, post‐transplant lymphoproliferative disorder (PTLD) and hemophagocytic lymphohistiocytosis (HLH), infection with Epstein–Barr virus (EBV) is a key mechanism: almost all PTLD in allogeneic stem cell transplantation (alloSCT) is caused by EBV‐related neoplastic lymphoproliferation, and secondary HLH is most frequently triggered by EBV infection. Therefore, concomitant EBV‐driven PTLD and HLH early after alloSCT require an approach to eliminate EBV and balance immune activation simultaneously. We report on a patient who developed simultaneous PTLD and signs of HLH on day 64 after alloSCT. Treatment was comprised of stopping cyclosporine, short‐course dexamethasone, and 3 courses of rituximab. The patient showed full recovery and complete remission of lymphadenopathy. This result indicates that immediate reduction in EBV‐carrying B cells by rituximab, suppression of general inflammation, and parallel support of reconstitution of long‐term T‐cell function, might be an appropriate therapeutic approach in this rare situation.